2019
DOI: 10.22491/rca.2019.3086
|View full text |Cite
|
Sign up to set email alerts
|

Umidade e aquecimento térmico na superação de dormência de sementes de dendezeiro tipo dura

Abstract: Green et al. Fontes de financiamento: Recursos custeados pelo Programa de Apoio à Fixação de Doutores no Amazonas FIXAM-AM-FAPEAM-AM-Edital nº 022/2013-Processo n o 062.01326.2014. E Embrapa-CPAA, pela disponibilização de infraestrutura e pessoal de apoio para desenvolvimento do projeto. Conflito de interesses: Os autores declaram não haver conflito de interesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…According to Orozco-Segovia et al (2003) and Meerow and Broschat (2017), variations in the germinability of palm seeds occur due to the genotype, maturation stage, and seed management. Although pretreatment is used routinely in oil palm (Elaeis guineensis), recent studies have shown variations as a function of the genotype, seed water content, temperature, and time of exposure (Fondom et al, 2010;Guerrero et al, 2011;Green et al, 2013;Lima et al, 2014;Green et al, 2019).…”
Section: Experiments 1 Germination As a Function Of The Thermal Pretreatment Of Diasporesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Orozco-Segovia et al (2003) and Meerow and Broschat (2017), variations in the germinability of palm seeds occur due to the genotype, maturation stage, and seed management. Although pretreatment is used routinely in oil palm (Elaeis guineensis), recent studies have shown variations as a function of the genotype, seed water content, temperature, and time of exposure (Fondom et al, 2010;Guerrero et al, 2011;Green et al, 2013;Lima et al, 2014;Green et al, 2019).…”
Section: Experiments 1 Germination As a Function Of The Thermal Pretreatment Of Diasporesmentioning
confidence: 99%
“…High temperatures seem to have some effect in overcoming seed dormancy in some palm trees (Rees, 1962;Comont and Jacquemard, 1977;Carpenter et al, 1993;Fondom et al, 2010;Guerrero et al, 2011;Green et al, 2013;Schlindwein et al, 2013;Lima et al, 2014;Rodrigues et al, 2014;Ferreira and Gentil, 2017;Green et al, 2019). Some associations between high temperatures and the physiological effect on seed dormancy have been pointed out, such as the reduction in the concentration of abscisic acid in the embryo and endosperm (Finch-Savage and Leubner-Metzger, 2006;Jiménez et al, 2008), the alteration in the balance between abscisic acid and other plant hormones (Cui et al, 2020), and changes in sensitivity to plant hormones (Jiménez et al, 2008).…”
Section: Experiments 2 Germination As a Function Of The Stratification Temperature Of Seedsmentioning
confidence: 99%
See 1 more Smart Citation